Minimally Invasive Autopsy Practice in COVID-19 Cases: Biosafety and Findings - Natalia Rakislova; Lorena Marimon; Mamudo R. Ismail; Carla Carrilho; Fabiola Fernandes; Melania Ferrando; Paola Castillo; Maria Teresa Rodrigo-Calvo; José Guerrero; Estrella Ortiz; Abel Muñoz-Beatove; Miguel J. Martinez; et al. (Pathogens, 2021)
Postmortem studies are crucial for providing insight into emergent diseases. However, a complete autopsy is frequently not feasible in highly transmissible diseases due to biohazard challenges. Minimally invasive autopsy (MIA) is a needle-based approach aimed at collecting samples of key organs without opening the body, which may be a valid alternative in these cases. We aimed to: (a) provide biosafety guidelines for conducting MIAs in COVID-19 cases, (b) compare the performance of MIA versus complete autopsy, and (c) evaluate the safety of the procedure. Between October and December 2020, MIAs were conducted in six deceased patients with PCR-confirmed COVID-19, in a basic autopsy room, with reinforced personal protective equipment. Samples from the lungs and key organs were successfully obtained in all cases. A complete autopsy was performed on the same body immediately after the MIA. The diagnoses of the MIA matched those of the complete autopsy. In four patients, COVID-19 was the main cause of death, being responsible for the different stages of diffuse alveolar damage. No COVID-19 infection was detected in the personnel performing the MIAs or complete autopsies. In conclusion, MIA might be a feasible, adequate and safe alternative for cause of death investigation in COVID-19 cases.